2011
DOI: 10.1007/s10526-011-9397-z
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Trichogramma: ITS2 DNA characterization and natural Wolbachia infection

Abstract: Egg parasitoids of the genus (Hymenoptera: Trichogrammatidae) are important natural enemies of many lepidopterous pests in agricultural and forest areas. Because the use of indigenous populations/species can significantly increase the biological control efficiency, the characterization of endemic populations and precise species identification is important. In this study, wasps were collected from parasitized eggs of several lepidopteran pests in Northern and Central Iran. Seven species were identified based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 60 publications
0
28
1
2
Order By: Relevance
“…Parthenogenesis inducing Wolbachia infecting Trichogramma species are exclusively found in the B supergroup (Pintureau et al, 2000;Poorjavad et al, 2012;Van Meer et al, 1999;Schulenburg et al, 2000;Werren et al, 1995b;Zhou et al, 1998). Several other Wolbachia infections in Trichogramma have been found that belong to the supergroup A, among others the infection in T. bourarachae and T. kaykai (LC110).…”
Section: Discussionmentioning
confidence: 99%
“…Parthenogenesis inducing Wolbachia infecting Trichogramma species are exclusively found in the B supergroup (Pintureau et al, 2000;Poorjavad et al, 2012;Van Meer et al, 1999;Schulenburg et al, 2000;Werren et al, 1995b;Zhou et al, 1998). Several other Wolbachia infections in Trichogramma have been found that belong to the supergroup A, among others the infection in T. bourarachae and T. kaykai (LC110).…”
Section: Discussionmentioning
confidence: 99%
“…However, the small size of these parasitoids (<1 mm long) and lack of clear diagnostic features make then difficult to identify, and this confusion can impede the implementation of effective biological control programs (Smith & Hubbes, 1986;Pinto et al, 1989;Pinto & Stouthamer 1994). Given the difficulties in distinguishing species of the genera, Trichogramma and Telenomus, molecular studies have gained importance in recent years (Yuliarti et al, 2002;Sümer et al, 2009;Poorjavad et al, 2012;Nasir et al, 2013). Therefore, with the advent of molecular techniques, DNA-based approaches have been used to generate molecular markers that are useful for the characterization of closely related or cryptic species for biological control work (Landry et al, 1993;Hoy et al, 2000;Chang at al., 2001).…”
Section: Feza Can Cengiz 1 Introductionmentioning
confidence: 99%
“…Trichogramma 속 ITS2 영역의 DNA 염기서열을 해독한 결과 종내 변이가 적 고 종간 염기서열 전체길이와 변이 차이가 커 종 구별을 위해 사 용될 수 있었다 Li et al, 2004). 그동안 많은 연구자들에 의해서 Trichogramma속 종들의 ITS2 전체 염기서열이 밝혀지고 GenBank 데이터베이스에 등록되고 있 으며 형태적 분류가 어려운 은폐종을 구별하여 왔다 (Amornsak et al, 1998;Silva et al, 1999;Stouthamer et al, 1999;Ciociola et al, 2001a, b;Li et al, 2004;Dang et al, 2005;Davies et al, 2006;Honda et al, 2006;Gariepy et al, 2007;Li, 2007;Kumar et al, 2009;Sumer et al, 2009;Jeong et al, 2010;Sumer et al, 2011;Karimi et al, 2012;Poorjavad et al, 2012;del Pino et al, 2013). 그러나 형태적으로 구별이 매우 힘든 T. minutum과 T.…”
Section: 방제하고자 하는 해충에 대해 효과가 좋은 기생벌 선발이 중요 한데 대량사육 과정에서 목적하지 않은 종이 섞unclassified
“…이중 옥수수에 가장 큰 문제 해충인 조명 나방의 알기생벌로는 수원지역에서 쌀좀알벌 (Lee et al, 1980;Jung et al, 2005)과 경남지역(진주, 하동, 밀양)에서 송충알벌 (Kim and Kim, 1991 Pinto and Stouthamer, 1994;Heimpel and de Boer, 2008;Poorjavad et al, 2012).…”
Section: 한국곤충명집(The Entomological Society Of Korea Andunclassified